Deubiquitination and Stabilization of PD-L1 by CSN5 - Lim, Seung-Oe; Li, Chia-Wei; Xia, Weiya; Cha, Jong-Ho; Chan, Li-Chuan; Wu, Yun; Chang, Shih-Shin; Lin, Wan-Chi; Hsu, Jung-Mao; Hsu, Yi-Hsin; Kim, Taewan; Chang, Wei-Chao; et al. (Cancer cell, 2016)
Pro-inflammatory cytokines produced in the tumor microenvironment lead to eradication of anti-tumor immunity and enhanced tumor cell survival. In the current study, we identified tumor necrosis factor alpha (TNF-α) as a major factor triggering cancer cell immunosuppression against T cell surveillance via stabilization of programmed cell death-ligand 1 (PD-L1). We demonstrated that COP9 signalosome 5 (CSN5), induced by NF-κB p65, is required for TNF-α-mediated PD-L1 stabilization in cancer cells. CSN5 inhibits the ubiquitination and degradation of PD-L1. Inhibition of CSN5 by curcumin diminished cancer cell PD-L1 expression and sensitized cancer cells to anti-CTLA4 therapy. [Display omitted] •TNF-α stabilizes cancer cell PD-L1 in response to chronic inflammation•Activation of NF-κB by TNF-α induces CSN5 expression leading to PD-L1 stabilization•CSN5 enzyme activity controls T cell suppression via PD-L1 deubiquitination•Destabilization of PD-L1 by CSN5 inhibitor curcumin benefits anti-CTLA4 therapy Lim et al. show that inflammation increases PD-L1 expression in tumors through TNF-α-mediated activation of NF-κB, leading to transactivation of CSN5. CSN5 reduces PD-L1 ubiquitination and stabilizes it. Inhibition of CSN5 cooperates with anti-CTLA4 to enhance anti-tumor T cell function and reduce tumor growth.